2022
DOI: 10.21037/atm-22-1958
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome dysbiosis in patients with hepatitis B virus-related hepatocellular carcinoma after extended hepatectomy liver failure

Abstract: Background: Hepatitis B virus-related hepatocellular carcinoma (B-HCC) negatively affects the gut microbiome. This study aimed to investigate the gut microbiome profiles and functions post-hepatectomy liver failure (PHLF) after extended hepatectomy (e-PHLF) to obtain valuable insights, identify potential diagnostic biomarkers, and assist in the treatment of this disease.Methods: B-HCC patients who underwent extended hepatectomy were consecutively recruited and divided into Group A (n=15) and Group B (n=15) bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…Yeast β-glucan had a significant impact on reducing the abundance of Bilophila in human cohorts, a microorganism associated with obesity. Methylobacterium-Methylorubrum was significantly enriched in post-hepatectomy liver failure [ 59 ]. The interactions among bile acid composition, gut microbiota, and metabolic phenotype were confirmed in the healthy and high-fat diet mice [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yeast β-glucan had a significant impact on reducing the abundance of Bilophila in human cohorts, a microorganism associated with obesity. Methylobacterium-Methylorubrum was significantly enriched in post-hepatectomy liver failure [ 59 ]. The interactions among bile acid composition, gut microbiota, and metabolic phenotype were confirmed in the healthy and high-fat diet mice [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a reduction in gut microbial diversity has been linked to the severity of the disease and poor health ( Wilmanski et al., 2019 ). Changes in the abundance of some gut bacteria can lead to the secretion of anti-inflammatory factors, thus accelerating disease progression ( Peng et al., 2022 ). Moreover, gut microbiome-derived metabolites such as LPS and bile acids could interact with liver immune cells leading to pathological effects ( Milosevic et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Note that all the records concerning HAV and HDV were excluded (Figure 1). Among the 12 included studies from PubMed, 1 was about HEV infection (Wu et al, 2020), 4 were about HCV infection (Aly et al, 2016;Taylor et al, 2020;Sultan et al, 2021;Ali et al, 2023), and 7 were HBV-related liver disorders (Wang et al, 2017;Liu et al, 2018;Liu et al, 2019;Ni et al, 2019;Chen et al, 2020;Zheng et al, 2020;Li et al, 2022). The remaining unpublished data was from BioProject and concerned HBV (BioProject accession number PRJEB32568).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…However, this study revealed a potential remedy: the restoration of specific microbial taxa capable of producing SCFAs, particularly acetate, effectively rescued liver regeneration in mice. This finding indicates potential implications for humans undergoing liver resection procedures, namely, that gut dysbiosis could adversely affect the regeneration process and subsequent patient survival ( 10 , 11 ).…”
mentioning
confidence: 88%